The pH-dependency of diastereomeric salt resolutions with amphoteric resolving agents. (1st January 2016) - Szeleczky, Zsolt; Bagi, Péter; Pálovics, Emese; Faigl, Ferenc; Fogassy, Elemér
We have analysed the role of pH in the diastereomeric resolution of racemic mandelic acid with (S)-phenylalanine and (R)-3-(aminomethyl)-5-methylhexanoic acid [(R)-Pregabalin] enantiomers. The adjusted pH had an effect on the optical purity and yield of the mandelic acid enantiomeric mixtures isolated from the diastereomeric salts. We showed that the pKa of the carboxyl group of the amphoteric resolving agents should be considered during the pH optimisation of diastereomeric salt resolutions.